The effect of topic selection on writing fluency among Japanese high school students - Lubold, Sarah Lin; Forbes, Sarah; Stevenson, Ian (Universitas Pendidikan Indonesia, 2016)
Written fluency and fluency building activities have been shown to promote linguistic choice and student voice development, increased ability to express ideas using complex grammatical structures and greater intrinsic motivation in English language learners. Since the 1970’s, process-oriented writing has been emphasized, yielding an amplified focus on meaning of student content over linguistic form precision. Current research of writing fluency must delve deeper into questions of student ownership of topic and the outcomes for low-risk activities that support fluency practice and encourage confidence building in students. The purpose of this replication study is to further explore previous findings on the effects of topic selection on writing fluency for high school English as foreign language learners. Building off of the work of Bonzo (2008), this study focused on a timed, non-graded writing activity administered to groups of Japanese engineering students in three departments: mechanical, electrical, and global engineering. The six subsequent samples for each participating student were analyzed using online text-analysis for total and unique word counts, providing data used to perform a t-test. Responses to bi-lingual student questionnaires, with prompts on self-perceived written English ability, self-efficacy and strategies for success while writing, provided additional insight into the facets of fluency. The results of these writing sessions offer both confirmation of and contrast to Bonzo’s original work, demonstrate increased student meaning making, and support the use of free writing activities in English language classrooms as a means by which student written fluency may be improved.